A Novel Low RCS Design Method for X-Band Vivaldi Antenna - XiaoXiang He; Teng Chen; Xin Wang (International Journal of Antennas and Propagation)
A novel low radar cross-section (RCS) design method is proposed, and its application on Vivaldi antenna that covers the entire X band is investigated. According to the difference of the current distribution on the radiator when the antenna radiates or scatters, the shape of the metal radiator is modified, so that maximally 19.2 dBsm RCS reduction is achieved which satisfied radiation performance. Simulated and measured results about gain, S11, and RCS are presented. As a result, the effectiveness of the presented low RCS design method is validated.